Efficacy and safety of sulforaphane-loaded emulsomes as tested on MCF7 and MCF10A cells - Karroum Reem; Üçışık Mehmet Hikmet (Türk Biyokimya Dergisi, 2024)
Sulforaphane is well-known for its anti-cancer properties particularly against breast, skin and prostate cancers. High sensitivity of sulforaphane to oxygen, heat, and alkaline conditions, as well as its poor oral bioavailability and water instability limit its use in medicine. In this study, we aim to overcome the prementioned limitations by encapsulating sulforaphane within a lipid-based drug delivery system, known as emulsome, and investigate the anti-cancer features of the attained formulation.